1990
DOI: 10.1093/oxfordjournals.humrep.a137193
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis and acrosome reaction-inducing activity of human cumulus cells

Abstract: The acrosome reaction of human spermatozoa is a prerequisite to fertilization. It has been hypothesized that secretions of cumulus cells could be involved in the induction of this sperm reaction. A source of variation in the in-vitro fertilization of human oocytes could be the maturational differences in the cumulus cells which affect the acrosome reaction. In order to investigate this possibility, we have studied the capability of secretions obtained from cumulus cells of different maturational stages to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Conditioned medium from cumulus cell culture induces acrosome reaction (40) and stimulates sperm motility (41). In this study, the acquisition of glycodelin immunoreactivity after penetration of the cumulus oophorus and Western blot analysis of the cumulus matrix demonstrate the presence of a small glycodelin-like molecule that interacts with the spermatozoa.…”
Section: Discussionmentioning
confidence: 55%
“…Conditioned medium from cumulus cell culture induces acrosome reaction (40) and stimulates sperm motility (41). In this study, the acquisition of glycodelin immunoreactivity after penetration of the cumulus oophorus and Western blot analysis of the cumulus matrix demonstrate the presence of a small glycodelin-like molecule that interacts with the spermatozoa.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, the cumulus oophorus is at an ideal position to modulate the fertilizing ability of spermatozoa passing through it. Indeed, the cumulus oophorus is known to affect human sperm functions (11)(12)(13)(14)(15)(16)(17)(18) and failure of its formation affects fertilization (8)(9)(10). The present study was designed to differentiate the roles of extracellular matrix and cumulus cells in affecting the functions of spermatozoa traversing the cumulus mass.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported that the cumulus cells affected sperm functions in vitro (11)(12)(13)(14)(15)(16)(17)(18). One report showed that coculture of human spermatozoa with cumulus cells significantly increased the fusion of spermatozoa with zona-free hamster oocyte (12).…”
mentioning
confidence: 99%
See 2 more Smart Citations